2015
DOI: 10.1093/nutrit/nuv027
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of food prices and diet cost to socioeconomic disparities in diet quality and health: a systematic review and analysis

Abstract: Context: It is well established in the literature that healthier diets cost more than unhealthy diets. Objective: The aim of this review was to examine the contribution of food prices and diet cost to socioeconomic inequalities in diet quality. Data Sources: A systematic literature search of the PubMed, Google Scholar, and Web of Science databases was performed. Study Selection: Publications linking food prices, dietary quality, and socioeconomic status were selected. Data Extraction: Where possible, review co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

41
776
6
33

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 925 publications
(856 citation statements)
references
References 168 publications
41
776
6
33
Order By: Relevance
“…The recent nationally representative UK nutrition survey also found that young people (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) have less confidence with cooking than other age groups in the UK (17) ; therefore they have more scope for improvement. However in our study, younger people (16)(17)(18)(19) improved in confidence less than 20-64 year olds. Additionally their fruit and vegetable intake improved less than 20-64 year olds.…”
Section: Confidence and Social Benefitscontrasting
confidence: 74%
“…The recent nationally representative UK nutrition survey also found that young people (19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) have less confidence with cooking than other age groups in the UK (17) ; therefore they have more scope for improvement. However in our study, younger people (16)(17)(18)(19) improved in confidence less than 20-64 year olds. Additionally their fruit and vegetable intake improved less than 20-64 year olds.…”
Section: Confidence and Social Benefitscontrasting
confidence: 74%
“…Sixty percent of food-insecure US households have participated in at least one federal food and nutrition assistance program, the largest being the Supplemental Nutrition Assistance Program (SNAP, called Cal-Fresh in California) [21]. SNAP benefits may be insufficient for people with chronic illness to access healthy foods, which tend to cost more than less healthy foods [22][23][24]. In addition, many food-insecure individuals are excluded from participation in the federal food safety-net: in 2012, almost 30% of food-insecure households in the US had incomes above the eligibility thresholds for federal nutrition assistance [25]; SNAP also excludes undocumented immigrants.…”
Section: Introductionmentioning
confidence: 99%
“…A number of considerations are paramount for ensuring that healthy diets are also sustainable diets – not only their environmental and health impact but also price, taste, culture and convenience. The links between socio‐economic class and diet quality are becoming well documented in different cultures 54, 55, 56, 57…”
Section: Consumersmentioning
confidence: 99%